2018
DOI: 10.2147/ceg.s121056
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor-refractory gastroesophageal reflux disease: challenges and solutions

Abstract: A significant percentage of patients with gastroesophageal reflux disease (GERD) will not respond to proton pump inhibitor (PPI) therapy. The causes of PPI-refractory GERD are numerous and diverse, and include adherence, persistent acid, functional disorders, nonacid reflux, and PPI bioavailability. The evaluation should start with a symptom assessment and may progress to imaging, endoscopy, and monitoring of esophageal pH, impedance, and bilirubin. There are a variety of pharmacologic and procedural intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 199 publications
1
35
0
9
Order By: Relevance
“…This observation is in accordance with a previous study showing that symptoms mainly decreased during the first 6 weeks of treatment . Interestingly, our statistical analysis did not report significant differences between the improvement in acid, nonacid, and mixed LPR, although nonacid LPR has long been suggested as reflux that is resistant to medical treatment . The good improvement of acid, nonacid, and mixed refluxes can be attributed to our personalized therapeutic approach consisting of the associated use of PPIs, alginate, and/or magaldrate according to the MII‐pH monitoring characteristics.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation is in accordance with a previous study showing that symptoms mainly decreased during the first 6 weeks of treatment . Interestingly, our statistical analysis did not report significant differences between the improvement in acid, nonacid, and mixed LPR, although nonacid LPR has long been suggested as reflux that is resistant to medical treatment . The good improvement of acid, nonacid, and mixed refluxes can be attributed to our personalized therapeutic approach consisting of the associated use of PPIs, alginate, and/or magaldrate according to the MII‐pH monitoring characteristics.…”
Section: Discussionsupporting
confidence: 91%
“…36 Interestingly, our statistical analysis did not report significant differences between the improvement in acid, nonacid, and mixed LPR, although nonacid LPR has long been suggested as reflux that is resistant to medical treatment. 37,38 The good improvement of acid, nonacid, and mixed refluxes can be attributed to our personalized therapeutic approach consisting of the associated use of PPIs, alginate, and/or magaldrate according to the MII-pH monitoring characteristics. According to our definition of nonacid LPR, the majority of patients with nonacid reflux had a few acidic reflux episodes.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Moreover, there are patients with GERD that is refractory to typical PPI therapy worldwide. 10 Overcoming these concerns requires the development of new drugs to treat GERD.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…Studies in patients with EE have shown high healing rates (88%‐96%) after 8‐week treatment with a PPI once daily . However, some patients may have endoscopic evidence of oesophagitis and/or reflux symptoms despite PPI therapy …”
Section: Introductionmentioning
confidence: 99%